The Effect of Variations In The Composition And Type of Adhesive For Mixed Peat And Gelam Wood Briquettes on The Physical Characteristics of The Briquettes - Andy Nugraha; Muhammad Zaini Arief; Randica Erwin M. Tampubolon; Faisal Putra Rahmadani (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
South Kalimantan has quite extensive peatlands, spread across various regions such as Barito Kuala, Banjar, Tapin, and Hulu Sungai Regencies. In these peatlands, gelam trees are often found growing rapidly and possessing various benefits, both for industrial and environmental purposes. With wise management, peat can be used as an environmentally friendly raw material for briquettes, while gelam wood can be utilized to improve the quality of the briquettes. In this study, mixed peat and gelam wood briquettes were made with various compositions (100%:0%, 80%:20%, 60%:40%, 50%:50%, 40%:60%, 20%:80%, and 0%:100%) and types of adhesives (palm sugar and damar resin). To determine the performance of the briquettes, physical characteristics were tested in the form of water content, ash content, volatile matter content, calorific value, and fixed carbon. Test results show that gelam increases the calorific value and volatile matter content but reduces the fixed carbon content, while peat increases the fixed carbon content but lowers the calorific value. Damar adhesive is superior in increasing calorific value and reducing ash content compared to palm sugar. The best briquette combination is ≥60% gelam with damar adhesive for fast, high-energy combustion. For slow, stable combustion, a dominant peat composition with damar adhesive is more suitable.